Upper Oligocene–Lower Miocene Gangdese Conglomerate Along the Yarlung-Zangbo Suture Zone and its Implications for Palaeo-Yarlung-Zangbo Initiation - Ai, Keke; Zhang, Kexin; Song, Bowen; Shen, Tianyi; Ji, Junliang (Frontiers in Earth Science, 2022)
The upper Oligocene–lower Miocene Gangdese conglomerate is deposited along the Yarlung-Zangbo suture zone, which extends 1,500 km from west to east and is located in the core area of the India–Eurasia plate collision zone. The Gangdese conglomerate records richly uplift and denudation histories of the Lhasa terrane and Tethyan Himalaya on both sides of the suture zone, thus revealing the growth process of the southern Tibetan Plateau during the Late Oligocene–Early Miocene. In this study, we documented the detailed sedimentology and chronology of the Gangdese conglomerate. The Gangdese conglomerate is dominated by conglomerate and sandstone, with minor volumes of siltstone and tuff deposited in an alluvial fan and fluvial system. Based on sedimentology and structural relationships, we suggest that the Gangdese conglomerate was deposited in an extensional tectonic environment in the early period and an extrusion tectonic environment in the late period, which was controlled by Indian slab shearing and breakoff during the Late Oligocene–Miocene. According to the new magnetostratigraphy and detrital zircon U-Pb dating, the main depositional age of the Gangdese conglomerate was likely the Late Oligocene–Early Miocene (26–18 Ma), and it trended younger from west to east. Moreover, paleocurrent data from the Gangdese conglomerate showed westward axial sediment transport; thus, we inferred that a westward axial palaeo-Yarlung-Zangbo River occurred along the whole Yarlung-Zangbo suture zone during the Late Oligocene–Early Miocene, and its flow was opposite to that of the current Yarlung-Zangbo River.